Strategic Pillars of MSME Sustainability: The Role of Digital Value Chains and Green Finance in Deli Serdang Regency - Nalom Siagian; Nurliani Siregar; Nenni Triana Sinaga (Manunggal Halim Jaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent a cornerstone of Indonesia’s economic structure, particularly in regions like Deli Serdang. Yet, MSMEs continue to face persistent challenges in digital transformation and environmental sustainability. This study investigates the synergistic role of digital value chains and green finance in enhancing the sustainability of MSMEs by focusing on their strategic capabilities. Using a quantitative approach with Structural Equation Modeling (SEM), data were collected from 400 MSME respondents across 22 sub-districts. SEM was chosen due to its suitability for analyzing complex relationships among latent constructs. The study addresses the following research question: To what extent does the integration of digitalization and green finance influence MSME sustainability through strategic capabilities? Findings indicate that digital adoption improves operational efficiency and market responsiveness, while green finance strengthens long-term sustainability orientations. Notably, their interaction creates a compounded effect on resilience and competitiveness. Practical implications suggest that this integrative model can guide policymakers, financial institutions, and local stakeholders in designing inclusive digital-financial ecosystems for MSMEs. The study extends the Resource-Based View and Triple Bottom Line frameworks by demonstrating their applicability in local MSME contexts.